FORMAÇÃO CONTINUADA DE PROFESSORES DE LÍNGUA MATERNA: NOVOS CAMINHOS, OUTRAS PRÁTICAS - CARNIN, ANDERSON; MACAGNAN, MARIA J. P.; CARNIN, ANDERSON; MACAGNAN, MARIA J. P. (Salão do Conhecimento, 2013)
Resumo